Efficiency of transport infrastructure and ICT development - Chang-Ho Yoon; Kyoung-Youn Na (International Telecommunications Society (ITS), 2013)
This study examines the impact of ICT growth on the productivity effects of transportation infrastructure. Using dynamic panel data of OECD member countries, the study finds econometrically meaningful results on examining the complementarity between ICT and transportation infrastructures. The network effect of growth of motorway infrastructure in advanced countries tends to accelerate when the ICT network grows beyond a certain threshold level.
Keywords: O47; O38; 330; Intelligent Transport System; ICT convergence; productivity growth; complementarity